Measuring the impact of genetic knowledge on intentions and attitudes of the community towards expanded preconception carrier screening. Issue 11 (1st August 2018) - Ong, Royston; Howting, Denise; Rea, Alethea; Christian, Hayley; Charman, Pauline; Molster, Caron; Ravenscroft, Gianina; Laing, Nigel George
Abstract : Background: Preconception carrier screening (PCS) provides the potential to empower couples to make reproductive choices before having an affected child. An important question is what factors influence the decision to use or not use PCS. Methods: We analysed the relationship between knowledge, attitudes and intentions to participate in PCS using logistic regression in 832 participants in Western Australia. Results: Two-thirds of participants said they would take the test, with 92% of these supporting screening for diseases reducing the lifespan of children and infants. Those who had good genetic knowledge were seven times more likely to intend to use PCS (p≤0.001), while those with high genetic knowledge were four times more likely to (p=0.002) and raised concerns such as insurance and confidentiality. Decreasing genetic knowledge correlated positively with religiosity and apprehension (p≤0.001), which correlated negatively with intention to use PCS (p≤0.001). Increasing genetic knowledge correlated positively with factors representing positive attitudes (p≤0.001), which correlated positively with intention to use PCS (p≤0.001). Many participants with good genetic knowledge nevertheless answered questions that tested understanding incorrectly. 80% of participants stated they would prefer to access the test through their general practitioners and 30% would pay up to $A200. Conclusions: Knowledge is instrumental in influencing participation. Having good genetic knowledge may not be enough to understand core concepts of PCS and may impact informed decision-making. This study recommends that continuous education of health professionals and thus the community, in PCS is crucial to reduce misconceptions.